The Implementation of English Curriculum at State Islamic College of Mandailing Natal: An Analysis of Challenges and Opportunities - Saputra, Muhammad Ari; Putriani, Zelly; Yolanda, Rizky; Ratnasari, Weni; Taqiyuddin, Taqiyuddin (STAIN Majene, 2025)
English proficiency has become an essential skill that significantly influences academic achievement, professional opportunities, and cross-cultural communication. This study investigates the implementation of the English Curriculum at the State Islamic College of Mandailing Natal, focusing on the challenges and opportunities inherent in the current pedagogical framework. Employing a qualitative case study approach, data were collected through semi-structured interviews and classroom observations, involving two lecturers, and thirty students. The analysis revealed that traditional, lecture-based teaching methods, resource limitations of material, and fragmented curriculum delivery pose significant challenges to effective language instruction. Conversely, the study identified promising opportunities, such as the integration of interactive teaching strategies, enhanced use of digital tools, and ongoing professional development for educators, which could bridge the gap between theoretical content and practical application. The findings suggest that targeted curriculum reforms are essential to create a more engaging and effective learning environment, ultimately enhancing students’ English language proficiency and preparing them for academic and professional success.